(untitled) (Al-Qamar, 2022)
The challenge of intolerance has surfaced as a significant concern for the Muslim Ummah, leading to various social and ideological issues. Islam actively discourages intolerance, advocating for patience, forbearance, and mutual respect. The teachings of Islam promote tolerance while denouncing extremism, radicalism, and inflexibility in all its forms. Although Islam permits intellectual and ideological differences, it firmly prohibits hostility, hatred, and conflict arising from such differences. At its core, true tolerance means that individuals can live together harmoniously, regardless of their beliefs, race, color, language, or nationality, without succumbing to prejudice or discrimination. It emphasizes the importance of respecting others’ rights and avoiding animosity towards those of different faiths and ideologies, even if one does not agree with their beliefs. Tolerance is a refined hallmark of civilization and a noble facet of human culture — a divine gift to humanity. A closer look at Islamic teachings shows that Islam not only advocates for tolerance but also serves as its leading champion. The Qur’an clearly states: “There is no compulsion in religion; truth stands out clear from error.”(Al-Baqarah 2:256) Likewise, the Seerah (biography) of the Prophet Muhammad ﷺ showcases remarkable examples of tolerance and compassion towards non-Muslims and adversaries. The Rightly Guided Caliphs (Khulafā’ al-Rāshidīn) also embodied these principles, setting shining examples of tolerance that have been etched in history. This research paper offers a thorough analytical exploration of tolerance through the lens of the Seerah of the Prophet Muhammad ﷺ and historical contexts, highlighting Islam’s universal message of peace, coexistence, and mutual respect.